Physical Correlates Students Volleyball Overhead Passing: Arm Strength, Trunk Flexibility, and Eye Hand Coordination - Akhmad, Noor; Hasanuddin, M Imran (LITPAM, 2022)
Overhead passing is a fundamental volleyball skill that requires controlled arm force, adequate trunk mobility, precise eye-hand coordination, and stable contact with the ball. This study examined the relationships between arm muscle strength, trunk flexibility, and eye-hand coordination with overhead passing ability among students in the volleyball learning context of SMA Nasional Makassar. A quantitative descriptive-correlational design was used with 60 valid student records. Data were collected through a push-up test, trunk forward-flexion test, wall bounce test, and 30-second volleyball overhead passing test. The data were analyzed using descriptive statistics, frequency distribution, the One-Sample Kolmogorov-Smirnov normality test, Pearson correlation, simple regression, and multiple regression. The results showed that all variables were normally distributed. Arm muscle strength was positively and significantly correlated with overhead passing ability (r = 0.657, p = 0.000), trunk flexibility was positively and significantly correlated with overhead passing ability (r = 0.457, p = 0.000), and eye-hand coordination was positively and significantly correlated with overhead passing ability (r = 0.589, p = 0.000). Simultaneously, the three predictors were significantly associated with overhead passing ability (R = 0.801, R Square = 0.642, F = 33.486, p = 0.000). These findings indicate that overhead passing ability is a multicomponent motor skill supported by strength, flexibility, and coordination. The study provides practical evidence for more targeted volleyball instruction and physical education assessment. Passing overhead adalah keterampilan dasar bola voli yang memerlukan kekuatan lengan yang terkontrol, mobilitas batang tubuh yang memadai, koordinasi mata-tangan yang tepat, dan kontak yang stabil dengan bola. Penelitian ini menguji hubungan antara kekuatan otot lengan, kelenturan badan, dan koordinasi mata tangan dengan kemampuan passing atas pada siswa dalam konteks pembelajaran bola voli SMA Nasional Makassar. Desain deskriptif-korelasi kuantitatif digunakan dengan 60 catatan siswa yang valid. Pengumpulan data dilakukan melalui tes push up, tes fleksi batang tubuh ke depan, tes pantulan dinding, dan tes passing overhead bola voli 30 detik. Analisis data menggunakan statistik deskriptif, distribusi frekuensi, uji normalitas One-Sample Kolmogorov-Smirnov, korelasi Pearson, regresi sederhana, dan regresi berganda. Hasil penelitian menunjukkan bahwa seluruh variabel berdistribusi normal. Kekuatan otot lengan berhubungan positif dan signifikan dengan kemampuan passing atas (r = 0.657, p = 0.000), kelenturan batang tubuh berhubungan positif dan signifikan dengan kemampuan passing atas (r = 0.457, p = 0.000), dan koordinasi mata-tangan berhubungan positif dan signifikan dengan kemampuan passing atas (r = 0.589, p = 0.000). Secara simultan ketiga prediktor berhubungan signifikan dengan kemampuan passing atas (R = 0.801, R Square = 0.642, F = 33.486, p = 0.000). Temuan ini menunjukkan bahwa kemampuan passing atas merupakan keterampilan motorik multikomponen yang didukung oleh kekuatan, fleksibilitas, dan koordinasi. Studi ini memberikan bukti praktis untuk pengajaran bola voli dan penilaian pendidikan jasmani yang lebih bertarget.